Design of 6-DOF Tomato Picking Lifting Platform - Pei Cao; Tianchi Wang; Liang Zhai; Shi’ao Niu; Li Liu; Yinggang Shi (Agriculture, 2022)
The tomato picking lifting platform is the carrier for the installation of the picking manipulator, which directly affects the operating range, speed, and picking effect of the picking manipulator. Based on the six degree of freedom motion platform, this paper designs a tomato lifting platform with automatic lifting and automatic leveling functions, which can accurately dock at the designated height to complete the picking operation, and verifies the validity of its parameters and the rationality of the operation movement. First, we analyzed the tomato planting mode and growth characteristics of greenhouse; determined the predetermined trajectory, mechanism travel, and motion form of the lifting platform to complete the lifting process during tomato picking; and determined the basic design parameters of the platform; Secondly, we used SolidWorks to build the three-dimensional model of the lifting platform, and imported it into ADAMS. We used the driving function to complete the dynamic simulation of the virtual prototype of the lifting platform, and obtained the force curve of the electric cylinder and hinge. We analyzed the force on the electric cylinder and hinge of the lifting platform to determine the rationality of the device design. Finally, according to the design requirements and simulation data, we made the prototype of the lifting platform, constructed the motion control system, and carried out relevant experiments. The experimental results show that the maximum rotation angle around the x, y, and z axis is ±10°, the maximum lifting distance is 15 cm, and the maximum load is 50 kg; meanwhile, the average time for the system to reach steady state is 0.309 s, the in-tilt error increases with the increase in biaxial tilt angle, with the maximum error of 1.09°, and the maximum mean square root error of 0.119°, which can meet the automatic operation requirements of the tomato picking manipulator.